Life insurance as an investor in Iraqi stock market - Jabbar Abed, lftekhar (Opción, 2019)
The study is aimed to investigate the financial literacy level of life insurance policyholders and to link the life insurance policyholder’s financial literacy with the intention to invest in the stock market. The data was collected through questionnaire from Iraqi life insurance policyholders and logistic regression was applied to analyze the relationship. Results revealed that there is a strong positive relationship between financial literacy of life insurance policyholders and intention to invest in the stock market. In conclusion, the stock market can collaborate with life insurance companies to enhance the investment flow in the stock market